Dehydroepiandrosterone Cocrystals with Improved Solubility and Bioavailability - Yihua Jiang; Yinxiang Cheng; Mengyuan Xia; Bingrui Zhang; Qiaoce Ding; Liye Lu; Jian-Rong Wang; Xuefeng Mei (MDPI AG, 2022)
Dehydroepiandrosterone (DHEA) is an FDA-approved food supplement used as an assisted reproductive sex hormone. The bioavailability is severely limited by its poor solubility (23 µg/mL). Herein, we aimed to modulate its solubility through cocrystallization. Eight cocrystals of DHEA with pyrocatechol (CAT), hydroquinone (HQ), resorcinol (RES), phloroglucinol (PG), 1,5-dihydroxy naphthalene (DHN), p-hydroxybenzoic acid (PHBA), gallic acid (GA), and 5-hydroxyisophthalic acid (5HIPA) were designed and synthesized. Some basic characterization tools, including powder X-ray diffraction, thermogravimetric analysis, differential scanning calorimetry, and Fourier transform infrared spectroscopy, were also applied in our work for basic analyses of cocrystals. It is indicated that DHEA-GA exhibits its superiority in dissolution and pharmacokinetic behaviors. While the area under the curve values of DHEA-GA is improved at the ratio of 2.2, the corresponding bioavailability of DHEA is expected to be accordingly increased.